Mycobacterium leprae in Daily Water Resources of Inhabitants Who Live in Leprosy Endemic Area of East Java - Wahyuni, Ratna; Adriaty, Dinar; iswahyudi, iswahyudi; Prakoeswa, Cita Rosita S.; Agusni, Indropo; izumi, shinzo (Institute of Topical Disease Universitas Airlangga, 2010)
Leprosy still a health problem in Indonesia, where many leprosy pocket areas still persists, especially in the eastern part of the country. Although the program of WHO – Multidrug Therapy (MDT) regiment has been conducted elsewhere since 1980s, only the prevalence can be reduced but not the incidence of new leprosy cases. Theoretically after the source of leprosy (the infectious leprosy cases) has been treated, no more transmission of the disease and should be no more new leprosy cases will be found. To explain this phenomenon, the non-human resource of M.leprae became a new topic of debates, especially the existence of bacteria in the environment. A field study of the existence of M.leprae in the environment of leprosy endemic area had been conducted in a leprosy endemic area of the northern part of East Java. The aim of the study is to find any correlation of the existence of these bacteria in the environment with the presence of leprosy patients who live in that area, in order to study its role in the transmission of the disease. Ninety water samples from wells in the house of inhabitants who live in one endemic sub district were collected. The owner of the well was interviewed whether any leprosy patients who routinely use the water for their daily life activities. Water samples were examined by Polymerase Chain Reaction (PCR) method to detect M.leprae DNA, using the LpF-LpR and Lp3-Lp4 nested primers (99bp). The PCR results showed positive band for M.leprae in 22 out of 90 (24%) water samples. Water samples from wells that used by leprosy patients showed positive PCR in 11/48 (23%), while 11 out of 42 (26%) water samples from wells that never been used by leprosy cases showed positive result. Statistically there was no difference (p>0.05) in the positivity of M.leprae between the two groups. It was concluded that the existence of M.leprae in the daily water resource was not correlated with the present of leprosy cases in the area. Possible symbiosis between protozoan and mycobacterium in the environment were discussed.